SHORT NOTICES (1966)
La Prière du Seigneur. By Heinz Schürmann. The Mother of God. Her physical Maternity: A Reappraisal. By Cletus Wessels. La Mystique et les Mystiques. By A. Ravier, S.J. and Others. Sous la direction de A. Ravier, S.J. Préface de Henri de Lubac, S.J. Summa Theologiae: St Thomas Aquinas; Latin text and English translation, introductions, notes Thomistic Epistemology. Vol. 2. By Georges van Riet. Translated by Donald. McCarthy, ph.d., and George E. Hertrich, m.a. Religious Psychology. By Vincent V. Herr, S.J. St Augustine and Being: A Metaphysical Essay. By James F. Anderson. The Coming of the Franciscans. By Thomas of Eccleston. Translated by Leo Sherley-Price. The Roman Catacombs and their Martyrs. By L. Hertling and E. Kirschbaum. The Council of Chalcedon and the Armenian Church. By Karekin Sarkissian. Histoire du Concile de Trente, Vol. 1. By Hubert Jedin. Jewish Prayer and Worship: an Introduction for Christians. By William W. Simpson. Carnet de Notes. By Jacques Maintain. The German Church Conflict. By Karl Barth. Gilbert Foliot and his Letters. By Adrian Morey and C. N. L. Brooke.